The next phases of the Migrante Project: Study protocol to expand an observatory of migrant health on the Mexico—U.S. border - Ana P. Martinez-Donate; Gudelia Rangel; Catalina Correa; Leah Bakely; Jesús Eduardo Gonzalez-Fagoaga; Ahmed Asadi González; Catalina Amuedo-Dorantes; Xiao Zhang; Carlos Magis-Rodriguez; Félice Lê-Scherban; Sylvia Guendelman; Emilio Parrado (Frontiers in Public Health, 2023)
BackgroundMexican migrants traveling across the Mexico-United States (U.S.) border region represent a large, highly mobile, and socially vulnerable subset of Mexican nationals. Population-level health data for this group is hard to obtain given their geographic dispersion, mobility, and largely unauthorized status in the U.S. Over the last 14 years, the Migrante Project has implemented a unique migration framework and novel methodological approach to generate population-level estimates of disease burden and healthcare access for migrants traversing the Mexico-U.S. border. This paper describes the rationale and history of the Migrante Project and the protocol for the next phases of the project.Methods/designIn the next phases, two probability, face-to-face surveys of Mexican migrant flows will be conducted at key crossing points in Tijuana, Ciudad Juarez, and Matamoros (N = 1,200 each). Both survey waves will obtain data on demographics, migration history, health status, health care access, COVID-19 history, and from biometric tests. In addition, the first survey will focus on non-communicable disease (NCD), while the second will dive deeper into mental health and substance use. The project will also pilot test the feasibility of a longitudinal dimension with 90 survey respondents that will be re-interviewed by phone 6 months after completing the face-to-face baseline survey.DiscussionInterview and biometric data from the Migrante project will help to characterize health care access and health status and identify variations in NCD-related outcomes, mental health, and substance use across migration phases. The results will also set the basis for a future longitudinal extension of this migrant health observatory. Analyses of previous Migrante data, paired with data from these upcoming phases, can shed light on the impact of health care and immigration policies on migrants’ health and inform policy and programmatic responses to improve migrant health in sending, transit, and receiving communities.